Yellow wattle (Acacia) - Three versions - English, Spanish, Indonesian - Ian Campbell; Ignacio Lopez-Calvo (PORTAL: Journal of Multidisciplinary International Studies)
Ian Campbell’s trilingual poem series explores the Acacia genus, Australia’s national floral emblem, across English, Spanish, and Indonesian. Inspired by Campbell’s family history and A.J. Campbell’s 1921 Golden Wattle – Our National Floral Emblem, the series examines the cultural and ecological significance of Acacia in Australia, Latin America, and Indonesia. Each version reflects linguistic and regional nuances, showcasing how the essence of a shared theme transforms across languages.